Comparison between an Interleaved Boost Converter and CUK Converter Fed BLDC Motor - V. Ramesh; Y. Kusuma Latha (International Journal of Power Electronics and Drive Systems (IJPEDS), 2015)
There is a great concern of torque ripple and power quality of three phase voltage source converter fed Permanent Magnet Brushless DC Motor (PMBLDCM). In this paper, two control strategies for BLDC motor drive has been investigated. One of the control strategies is based on PFC - CUK converter fed PMBLDCM drive and another one is PFC- interleaved boost converter fed BLDC motor drive. Comparison has been made between the two control stragies in terms of Torque ripple, Total harmonic distortion (THD) and power factor for different operating speeds. The proposed work as been implemented under MATLAB/simulink environment. Simulation results are presented to validate proposed work. From the results, it is observed that PFC interleaved Boost converter fed BLDC motor drive is more effective compared to CUK converter fed BLDC motor drive.